Preclinical assessment and randomized Phase I study of CT-P63, a broadly neutralizing antibody targeting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Issue 1 (31st December 2022) - Seo, Ji-Min; Kang, Bobin; Song, Rina; Noh, Hanmi; Kim, Cheolmin; Kim, Jong-In; Kim, Minsoo; Ryu, Dong-Kyun; Lee, Min-Ho; Yang, Jeong-Sun; Kim, Kyung-Chang; Lee, Joo-Yeon; et al.
ABSTRACT: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in significant morbidity and mortality worldwide. Despite a successful vaccination programme, the emergence of mutated variants that can escape current levels of immunity mean infections continue. Herein, we report the development of CT-P63, a broad-spectrum neutralizing monoclonal antibody. In vitro studies demonstrated potent neutralizing activity against the most prevalent variants, including Delta and the BA.1 and BA.2 sub-lineages of Omicron. In a transgenic mouse model, prophylactic CT-P63 significantly reduced wild-type viral titres in the respiratory tract and CT-P63 treatment proved efficacious against infection with Beta, Delta, and Omicron variants of SARS-CoV-2 with no detectable infectious virus in the lungs of treated animals. A randomized, double-blind, parallel-group, placebo-controlled, Phase I, single ascending dose study in healthy volunteers (NCT05017168) confirmed the safety, tolerability, and pharmacokinetics of CT-P63. Twenty-four participants were randomized and received the planned dose of CT-P63 or placebo. The safety and tolerability of CT-P63 were evaluated as primary objectives. Eight participants (33.3%) experienced a treatment-emergent adverse event (TEAE), including one grade ≥3 (blood creatine phosphokinase increased). There were no deaths, treatment-emergent serious adverse events, TEAEs of special interest, or TEAEs leading to study drug discontinuation in the CT-P63 groups. Serum CT-P63 concentrations rapidly peaked before declining in a biphasic manner and systemic exposure was dose proportional. Overall, CT-P63 was clinically safe and showed broad-spectrum neutralizing activity against SARS-CoV-2 variants in vitro and in vivo .